Differential Host Immune Responses to Epidemic and Endemic Strains of Shigella dysenteriae Type 1 - Sayem, Mohammad Abu; Ahmad, Shaikh Meshbahuddin; Rekha, Rokeya Sultana; Sarker, Protim; Agerberth, Birgitta; Talukder, Kaisar Ali; Raqib, Rubhana (Journal of Health, Population and Nutrition, 2011)
Shigella dysenteriae type 1 causes devastating epidemics in developing countries with high case-fatality rates in all age-groups. The aim of the study was to compare host immune responses to epidemic (T2218) and endemic strains of S. dysenteriae type 1. Shigellacidal activity of serum from rabbits immunized with epidemic or endemic strains, S. dysenteriae type 1-infected patients, and healthy adult controls from Shigellaendemic and non-endemic regions was measured. Immunogenic cross-reactivity of antibodies against Shigella antigens was evaluated by Western blot analysis. Oxidative burst and phagocytic responses of monocytes and neutrophils to selected S. dysenteriae type 1 strains were assessed by flow cytometry. Rabbit antisera against epidemic strain were less effective in killing heterologous bacteria compared to endemic antisera (p=0.0002). Patients showed an increased serum shigellacidal response after two weeks of onset of diarrhoea compared to the acute stage (3-4 days after onset) against their respective homologous strains; the response against T2218 and heterologous endemic S. dysenteriae type 1 strains was not significant. The serum shigellacidal response against all the S. dysenteriae type 1 strains was similar among healthy controls from endemic and non-endemic regions and was comparable with the acute stage response by patients. Compared to endemic strains of S. dysenteriae type 1, T2218 was significantly resistant to phagocytosis by both monocytes and neutrophils. No obvious differences were obtained in the induction of oxidative burst activity and cathelicidin-mediated killing. Cross-reactivity of antibody against antigens present in the epidemic and endemic strains showed some differences in protein/peptide complexity and intensity by Western blot analysis. In summary, epidemic T2218 strain was more resistant to antibody-mediated defenses, namely phagocytosis and shigellacidal activity, compared to endemic S. dysenteriae type 1 strains. Part of this variation may be attributed to the differential complexity of protein/peptide antigens. Key words: Disease models, Animal; Dysentery, Bacillary; Immune response; Shigella dysenteriae DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8896 JHPN 2011; 29(5): 429-437